2013
DOI: 10.4172/jmso.1000104
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1* Allele Frequencies in Pediatric, Adolescent and Adult-Onset Multiple Sclerosis Patients, in a Hellenic Sample. Evidence for New and Established Associations

Abstract: Studies in many populations consistently have showed that the human leukocyte antigens (HLA) and especially the DRB1 * 15 allele has by far the strongest genetic association with multiple sclerosis (MS). The aim of this study was to investigate the role of HLA-DRB1 * alleles in MS risk/resistance and onset. A sample of 165 Hellenic MS patients (18 with pediatric-, 24 with adolescent-and 123 with adult-onset MS) and 107 healthy volunteers were examined with molecular techniques. Comparisons were made according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
1
13
1
2
Order By: Relevance
“…HLA-DRB1*11 was also found to be protective in the Brazilian [ 20 ], Canadian [ 21 ] and Greek [ 22 ] populations. The protective role of the HLA-A*02:01 has been confirmed in many different populations and remains the most widely studied HLA Class I allele in MS [ 23 ].…”
Section: Genetic Predisposition and Immunopathogenetic Function Of Hlmentioning
confidence: 99%
“…HLA-DRB1*11 was also found to be protective in the Brazilian [ 20 ], Canadian [ 21 ] and Greek [ 22 ] populations. The protective role of the HLA-A*02:01 has been confirmed in many different populations and remains the most widely studied HLA Class I allele in MS [ 23 ].…”
Section: Genetic Predisposition and Immunopathogenetic Function Of Hlmentioning
confidence: 99%
“…Regarding HLA alleles, DRB1*15 association with early-onset MS has been noted by a series of studies [12,[19][20][21][22]. In 2000, a study of 286 Norwegians MS patients demonstrated that the HLA-DR2, DQ6 haplotype is negatively correlated with age at diagnosis [23].…”
Section: Hla Allele Distribution In Early-onset Ms Worldwidementioning
confidence: 99%
“…Anagnostouli et al attributed this discrepancy either to a possible parent of origin effect, relying on Ramagopalan et al' observation that only maternally transmitted DRB1*15 promotes a lower age of MS [44], or to fluctuations of vitamin D levels among different populations[45]. New findings in this former are the putative predisposing role of DRB1*03 allele and the protective role of the DRB1*16 allele for early-onset MS[20].…”
mentioning
confidence: 99%
“…Recent studies have further established the role of HLA-DRB1*15:01 in early-onset (pediatric and adolescent) MS (EOMS), which accounts for 3–5% of all MS cases, while the role of HLA-DRB1*04 and HLA-DRB1*03 remains to be clarified [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study attempts to expand the existing data on HLA and MS by investigating the influence of HLA-DPB1* alleles on disease risk and resistance in a Hellenic sample of 100 patients of both EOMS and AOMS, using healthy controls (HC) for comparisons, given the pre-existing difference in HLA-DRB1 allele frequencies in EOMS and AOMS in our ethnic group [ 11 ] and the total absence of information on HLA-DPB1 genotyping in the Hellenic MS population.…”
Section: Introductionmentioning
confidence: 99%